Perceived cancer-related stigma among Arab patients: A cross-sectional study - Fawwaz Alaloul; Mohammad Al Qadire; Omar Al Omari; Sulaiman Al Sabei; Mudhar Al Adawi; Zamzam Al-Habsi (PLoS ONE, 2025)
Purpose The primary objective of this study was to examine the perceived stigma experienced by patients with cancer within the context of Arabic and Islamic culture. Methods A cross-sectional study was conducted with 190 Arab Muslim patients with cancer from two government-designated hospitals. Participants completed the Social Impact Scale, and descriptive statistics were calculated for the four subdomains associated with perceived stigma. Results The average stigma score was 82.36, indicating a high level of perceived stigma. The dimensions of stigma, ranked in descending order, were as follows: social rejection (M = 3.69), financial security (M = 3.35), isolation (M = 3.34), and internalized shame (M = 3.16). Conclusion The study findings indicate that Muslim Arab patients with cancer experience significant stigmatization. Social rejection was the most significant dimension of stigma, followed by concerns regarding financial security, feelings of isolation, and internalized shame. Culture and religion can play a vital role in influencing perceptions and experiences of cancer, leading to varying levels of stigma associated with the disease across diverse cultural backgrounds.